Indonesia–English Bilingual Visual Question Answering Using Partial Fine-Tuning on a ViT-GPT2 Architecture - Anas Anas; Hazriani Hazriani; Yuyun Yuyun; Syamsul Rijal; Tirta Chiantalia Sharief (Journal of Applied Informatics and Computing, 2026)
Visual Question Answering (VQA) is a multimodal task that integrates visual understanding and natural language processing to generate answers based on information contained in an image. Most existing VQA research focuses on the English language and general-domain datasets, limiting its applicability to bilingual environments and domain-specific scenarios. This study proposes an Indonesia–English bilingual VQA model based on the VisionEncoderDecoderModel architecture, which combines a Vision Transformer (ViT) as the visual encoder and an Indonesian GPT-2 model as the language decoder. Bilingual capability is achieved through the introduction of special language tokens, <id> and <en>. The model is trained using a combination of the bilingual VQAv2 and bilingual LosariVQAv1 datasets, representing general-domain and local tourism-domain knowledge, respectively. Four fine-tuning strategies are evaluated: Encoder Freeze, Full Fine-Tuning, Partial-4, and Partial-6. Experimental results show that the Partial-6 strategy achieves the best performance on LosariVQAv1, obtaining an Exact Match score of 26.67%, a BLEU score of 26.80%, and a CIDEr score of 292.67, while maintaining competitive performance on VQAv2 with an Exact Match score of 41.26%. Cross-language evaluation reveals only a small performance gap between Indonesian and English. The findings indicate that partial fine-tuning provides a better balance between generalization capability and domain adaptation than the other fine-tuning strategies evaluated in this study.